Ashviny Murugan, daughter of a lorry driver, receives Royal Education Award Pingat Jaya Cemerlang - Nadira Hana, Abdul Hamid (2022)
KUANTAN, 17 March 2022 - The daughter of a lorry driver was proud when she received the Royal Education Award (Pingat Jaya Cemerlang) at the 15th Universiti Malaysia Pahang (UMP) Convocation Ceremony.